Multi-locus sequencing reveals a novel Bartonella in mammals from the Superorder Xenarthra - Calchi, Ana Cláudia [UNESP]; Vultão, Juliana Gaboardi; Alves, Mario Henrique; Yogui, Débora Regina; Desbiez, Arnaud Leonard Jean; Amaral, Renan Bressianini [UNESP]; Santi, Mariele [UNESP]; Teixeira, Marta Maria Geraldes; Werther, Karin [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Hindawi, 2020)
The superorder Xenarthra consists of sloths, anteaters and armadillos, mammals originated from South America and currently distributed from the south of North America to the south of South America. The present study aimed to investigate the occurrence and genetic diversity of Bartonella spp. in blood and spleen samples from free-living Xenarthra mammals in the states of São Paulo (SP), Mato Grosso do Sul (MS), Rondônia (RO) and Pará (PA). Based on a quantitative real-time PCR (qPCR) assay, a Bartonella spp. nuoG gene fragment was detected in 1.51% (5/330) of the samples: 4 six-banded armadillos (Euphractus sexcinctus) sampled in the MS and 1 southern tamandua (Tamandua tetradactyla) sampled in the PA. Eight sequences (5 ftsZ, 2 gltA and 1 rpoB) were obtained in the conventional PCR assays. In both phylogenetic analyses based on Bayesian and distance (SplitsTree) methods, the obtained ftsZ, gltA and rpoB sequences were positioned in a distinct clade, but related to B. washoensis. The analysis of SplitsTree and genotype networks based on B. washoensis sequences from several hosts from various localities of the world showed that the sequences of the present study were allocated in a group separated from the other sequences, indicating that they probably originated from median vectors and large numbers of mutational events. Additionally, the analyses performed by BLAST showed low percentages of identities of the sequences obtained in the present study when compared to those previously deposited in GenBank. Therefore, we propose a new Candidatus to Bartonella occurring in Xenarthra in Brazil. The present study was the first to report the occurrence of Bartonella sp. in mammals of the superorder Xenarthra in the world, and it was the first to describe a new Candidatus related to B. washoensis in Brazil.
Keywords: anteater; armadillo; bartonella; Brazil; genetic diversity; sloth